Qualitative and Quantitative Analysis of Aflatoxins in Dry Fruits and Nuts from Central India - Patel, Anju; Pandey, Akhilesh Kumar; Mishra, Ravi Prakash (Defence Life Science Journal, 2020)
In central part of India, dry fruits and nuts are mostly sold in loose conditions and hence may get fungal infections, and may have aflatoxins to the levels beyond the safe limits. The present study is an attempt to showcase the present scenario of aflatoxins in dry fruits and nuts from Central India, both qualitatively and quantatively. Out of 84 samples, 15 were found to have the presence of at least one aflatoxin. HPLC detection showed that AFB1 is the major aflatoxin. The total aflatoxins were found in the range of 25.4 - 393.51 μg kg-1, which is beyond the safe limit set by regulatory authorities. Further, dry figs were the most contaminated among tested dry fruits, and 5 out 12 samples (41.6%) were contaminated, followed by cashew nuts (33.3%). Samples sold in loose packing were found more contaminated with aflatoxins. The study advocates that selling of such dry fruits in loose form should be banned by the regulatory authorities.